IDENTIFICATION OF RICE (Oryza sativa L.) VARIETIES SUITABLE FOR DRY SEASON AND WET SEASON PLANTING - Sumarno Sumarno; Entis Sutisna (Indonesian Agency for Agricultural Research and Development, 2010)
Rice planting on dry and wet seasons faces a specific climatological characteristic, which affects directly on rice growth and yield. Fifteen rice genotypes were evaluated for their seasonal planting adaptation at Sukamandi Experimental Station, Subang, West Java, during the dry and wet seasons of 2009-2010. Randomized complete block design with three replications was applied on the experiment. Plot size was 4 m x 6 m and plant spacing was 20 cm x 20 cm. Standard agronomic practices were applied on both planting season experiments. Data were collected for major morphological traits, days to grain maturity and grain yield, measured on wet and dry basis (11% moisture content). Data were analysed for analyses of variance for each season and for combined seasons, and mean values separation of the variable used the 5% Duncan Multiple Range Test. Correlation between grain yields and morphological variable data were computed for each season and for combined seasons. The correlation coefficients of variables and grain yield were partitioned into direct and indirect causes using path analyses. Combined analyses of variances indicated significant effects of genotypes, seasons and genotypes x seasons interaction for almost all variables, including grain yields, suggesting there were seasonal adaptation specificity among genotypes. Five genotypes were identified as suitable for dry season planting, and nine genotypes as suitable for wet season planting. Among those genotypes, three genotypes, namely Mekongga, Inpari-10 and OM 5240 were suitable for both dry and wet season planting. Ciherang and Cigeulis varieties were more suitable for dry season, while Cibogo, Inpari-1, Inpari-3, Inpari-5, and Inpari-8 were more suitable for wet season planting. Adopting the most productive rice varieties for planting on dry or wet season as was suggested on this research should increase rice production substantially. To facilitate the availability of varieties adapted for a specific planting season, rice breeding should purposedly apply a directional selection of lines suitable for specific planting season, starting on the early generation of selection.